SYSTEMATIC LITERATURE REVIEW: EKSPLORASI ETNOMATEMATIKA PADA MOTIF BATIK - Feni Okti Yolanda; Aan Putra (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
This article aims to describe the results of ethnomathematical exploration on batik patterns that can be used as teaching materials for students. The research method chosen in this study is the SLR (Systematic Literature Review) method. The SLR method is used to identify, review, evaluate, and interpret all available research with topic areas of interest. Data collection is done by documenting and reviewing all articles related to ethnomathematics on batik patterns. The articles used were 10 articles. The results showed that ethnomathematics-based mathematics learning on batik patterns could be used in the learning process and had a positive impact on students.